The effect of herbage availability and season of year on the rate of liveweight loss during weighing of fasting ewe lambs - Semakula J; Corner-Thomas RA; Morris ST; Blair HT; Kenyon PR (Massey University)
Sheep (Ovis aries) liveweight and liveweight change can contain errors when collection procedures are not standardized, or when there are varying time delays between removal from grazing and weighing. A two-stage study was conducted to determine the effect of herbage availability and season of year on the rate of liveweight loss during fasting and to develop and validate correction equations applied to sets of delayed liveweights collected under commercial conditions. Results showed that ewe lambs offered the Low herbage availability lost up to 1.7 kg and those offered the Medium or High herbage availability lost 2.4 kg during 8 h of delayed weighing without access to feed or drinking water. The rate of liveweight loss varied by season, herbage availability and farm (p < 0.05). Applying correction equations on matching liveweight data collected under similar conditions, provided more accurate estimates (33-55%) of without delay liveweight than using the delayed liveweight. In conclusion, a short-term delay prior to weighing commonly associated with practical handling operations significantly reduced the liveweight recorded for individual sheep. Using delayed liveweights on commercial farms and in research can have significant consequences for management practices and research results globally, therefore, liveweight data should be collected without delay. However, when this is not feasible delayed liveweights should be corrected, and in the absence of locally formulated correction equations, the ones presented in this paper could be used.
Keywords: accuracy; correction equations; gut-fill; liveweight; liveweight loss; 0701 Agriculture, Land and Farm Management